Buddhist learning in South Asia : education, religion, and culture at the ancient Śrī Nālandā Mahāvihāra. - Kumar, Pintu (Lexington Books, 2018)
This interdisciplinary study provides a broad analysis of Śrī Nālandā Mahāvihāra, the Buddhist learning center, during the first millennium AD. Drawing from history, archaeology, and religious studies, the author examines its role both as a religious and educational institution and investigates the impact of nationalist interpretations of the site.